Preparation and Embedding Characterization of Hydroxypropyl-β-cyclodextrin/Menthyl Acetate Microcapsules with Enhanced Stability - Xiaoqing Huang; Honghui Guo; Quanling Xie; Wenhui Jin; Runying Zeng; Zhuan Hong; Yiping Zhang; Yucang Zhang (MDPI AG, 2023)
Objective: Hydroxypropyl-β-cyclodextrin (HP-β-CD)/menthyl acetate (MA) microcapsules were developed to overcome the volatile and unstable defects of MA and improve the ease of use and storage. Methods: MA microcapsules were prepared via spray drying using HP-β-CD as the wall material. The embedding rate of MA microcapsules was determined through gas chromatography. The embedding characteristics were studied using phase solubility and nuclear magnetic resonance (NMR). The stability was characterized via differential scanning calorimetry (DSC) and the release and retention rates of MA microcapsules at different temperatures. Results: The embedding rate of HP-β-CD /MA microcapsules was 96.3%. The Gibbs free energy change, enthalpy change and entropy change of the embedding reaction between HP-β-CD and MA were all less than zero, indicating that the embedding process was a spontaneous exothermic reaction. NMR spectra showed that MA entered the cavity of HP-β-CD through the large opening end and interacted with the inner wall of the small opening end. DSC and the release and retention rates of MA microcapsules at different temperatures showed that the stability of MA was significantly enhanced after being embedded in HP-β-CD. Conclusion: The HP-β-CD/MA microcapsules are able to significantly improve the stability of MA and reduce the volatilization of MA.